2015
DOI: 10.1038/leu.2015.206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PTEN abnormalities on outcome in pediatric patients with T-cell acute lymphoblastic leukemia treated on the MRC UKALL2003 trial

Abstract: PTEN gene inactivation by mutation or deletion is common in pediatric T-cell acute lymphoblastic leukemia (T-ALL), but the impact on outcome is unclear, particularly in patients with NOTCH1/FBXW7 mutations. We screened samples from 145 patients treated on the MRC UKALL2003 trial for PTEN mutations using heteroduplex analysis and gene deletions using single nucleotide polymorphism arrays, and related genotype to response to therapy and long-term outcome. PTEN loss-of-function mutations/gene deletions were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 38 publications
0
60
0
Order By: Relevance
“…36 This was not confirmed in the MRC UKALL2003 trial for pediatric T-ALL; RAS and/or PTEN aberrations also did not change the favorable outcome of patients with NOTCH1/FBWX7 mutations. 44 Taken together, these findings suggest that PTEN aberrations may represent a general, poor prognostic factor in T-ALL.…”
Section: Discussionmentioning
confidence: 79%
“…36 This was not confirmed in the MRC UKALL2003 trial for pediatric T-ALL; RAS and/or PTEN aberrations also did not change the favorable outcome of patients with NOTCH1/FBWX7 mutations. 44 Taken together, these findings suggest that PTEN aberrations may represent a general, poor prognostic factor in T-ALL.…”
Section: Discussionmentioning
confidence: 79%
“…Neither PTEN nor K/N-RAS genotype significantly impacted outcome, and there was no evidence that they changed the highly favorable outcome of patients with double N/F mutations. 44 Application of the N/F/R/P classifier presented here to this cohort did, however, show a trend towards an inferior OS outcome, but not an inferior relapse-free survival outcome. The reasons for this discordance merit closer examination but potentially include minor treatment variables, the relatively small size of the UKALL cohort, and/or different molecular techniques and/or interpretation, because the incidence of PTEN abnormalities was slightly higher in the UKALL2003 cohort (22%) than the FRALLE2000 cohort (14%).…”
mentioning
confidence: 93%
“…The incidence of N/F (61%), PTEN (14%) and K/N RAS (8%) aberrations were similar to other pediatric T-ALL series. 22,24,40,41,43,44 Recently, 145 pediatric T-ALLs treated on the UKALL2003 trial were tested for PTEN/K/N-RAS and N/F mutations. Neither PTEN nor K/N-RAS genotype significantly impacted outcome, and there was no evidence that they changed the highly favorable outcome of patients with double N/F mutations.…”
mentioning
confidence: 99%
“…45 As already noted for JAK/STAT, RAS/PTEN alterations are a common feature of T-ALL; their prognostic impact is still controversial in childood. [46][47][48][49] In particular, in their study of children treated with the Berlin-FrankfurtMunster protocol, Bandapalli et al reported that patients with PTEN and NOTCH1 mutations had a marked sensitivity to induction treatment and excellent long-term outcome, similar to that of patients with NOTCH1 mutations only and more favorable than that of patients with PTEN mutations only. 48 The study of Jenkinson et al on pediatric patients treated on the Medical Research Council UKALL2003 trial showed that neither PTEN nor RAS genotypes have a significant impact on response to therapy or long-term outcome; it was also shown that neither PTEN nor RAS genotypes affect the highly favorable outcome of patients with concomitant NOTCH1/FBXW7 mutations.…”
Section: A B Cmentioning
confidence: 99%
“…48 The study of Jenkinson et al on pediatric patients treated on the Medical Research Council UKALL2003 trial showed that neither PTEN nor RAS genotypes have a significant impact on response to therapy or long-term outcome; it was also shown that neither PTEN nor RAS genotypes affect the highly favorable outcome of patients with concomitant NOTCH1/FBXW7 mutations. 49 Conversely, the GRAALL group reported that the favorable prognostic significance of NOTCH1/FBXW7 mutations was restricted to adult patients without RAS/PTEN abnormalities. In fact, K/N-RAS mutations and/or PTEN gene alterations have been associated with poor prognosis.…”
Section: A B Cmentioning
confidence: 99%